2018
DOI: 10.20900/jpbs.20180012
|View full text |Cite
|
Sign up to set email alerts
|

Let’s Talk about the Association between Schizophrenia Polygenic Risk Scores and Cognition in Patients and the General Population: A Review

Abstract: In the late 19th century, Emil Kraepelin divided endogenous psychosis into manic-depressive psychosis and dementia praecox. The latter term described individuals with schizophrenia and highlights cognitive deficits as a core feature of this illness. Since first degree relatives show lower cognitive performance than healthy controls, but better performance than patients, cognitive functions are discussed as potential endophenotypes for schizophrenia. During the last years, several studies have explored the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Previous research revealed similar findings ( Dauvermann and Donohoe, 2018 ). These inconsistencies could be due to individual stress responses, different coping strategies, and variability of cognitive performance in schizophrenia, which is partly explained by genetic risk ( Comes et al, 2019 ; Engen et al, 2020 ; Popovic et al, 2019 ; Richards et al, 2019 ; Schaupp et al, 2018 ). In addition, protective and unfavorable environmental factors and related epigenetic effects might also play a role ( Brown, 2011 ; Popovic et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research revealed similar findings ( Dauvermann and Donohoe, 2018 ). These inconsistencies could be due to individual stress responses, different coping strategies, and variability of cognitive performance in schizophrenia, which is partly explained by genetic risk ( Comes et al, 2019 ; Engen et al, 2020 ; Popovic et al, 2019 ; Richards et al, 2019 ; Schaupp et al, 2018 ). In addition, protective and unfavorable environmental factors and related epigenetic effects might also play a role ( Brown, 2011 ; Popovic et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%